Cervical spine fractures in ankylosing spondylitis: a case report and literature review: Zlomi vratne hrbtenice pri ankilozantnem spondilitisu: prikaz primera in pregled literature - Kunej, Tomi; Movrin, Igor (Acta Medico-Biotechnica, 2021)
Purpose: Cervical spine fractures are a major cause of morbidity and mortality in patients with ankylosing spondylitis. These fractures are usually the cause of minor trauma and unstable in nature and, therefore, should be treated surgically.Case report: Although the optimal choice of treatment remains a matter of discussion, combined anteroposterior or 360° fixation should be performed. Here, a case of a 48–year old male patient with an isolated C6 fracture that was treated with 360° fixation with good results is presented along with a review of the current literature on this topic.Conclusion: Fractures of the cervical spine in ankylosing spondylitis should be treated with a 360° fixation, as this method enables the best treatment results.
Keywords: Ankylosing spondylitis; cervical spine; fracture